2013
DOI: 10.1172/jci71353
|View full text |Cite
|
Sign up to set email alerts
|

Sound preconditioning therapy inhibits ototoxic hearing loss in mice

Abstract: Therapeutic drugs with ototoxic side effects cause significant hearing loss for thousands of patients annually. Two major classes of ototoxic drugs are cisplatin and the aminoglycoside antibiotics, both of which are toxic to mechanosensory hair cells, the receptor cells of the inner ear. A critical need exists for therapies that protect the inner ear without inhibiting the therapeutic efficacy of these drugs. The induction of heat shock proteins (HSPs) inhibits both aminoglycoside-and cisplatin-induced hair ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 29 publications
1
60
2
1
Order By: Relevance
“…Mice were 2 months old at the beginning of each injection protocol, which has been described. 49 Briefly, cisplatin (APP Pharmaceuticals, LLC) was administered via intraperitoneal injection, 4 mg/kg each day for 4 days, followed by 10 days of recovery. Three such cycles of cisplatin were administered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were 2 months old at the beginning of each injection protocol, which has been described. 49 Briefly, cisplatin (APP Pharmaceuticals, LLC) was administered via intraperitoneal injection, 4 mg/kg each day for 4 days, followed by 10 days of recovery. Three such cycles of cisplatin were administered.…”
Section: Methodsmentioning
confidence: 99%
“…Preand post-injection auditory brainstem response (ABR) testing was performed to examine hearing sensitivity in both cisplatin-and kanamycin-treated groups, as described. 49 ABR testing was also performed for each control group.…”
Section: Methodsmentioning
confidence: 99%
“…A new approach called sound preconditioning has been developed to inhibit cisplatin-induced hearing loss (Roy et al, 20 13). Cochlear expression of heat shock proteins (HSPs) can be induced by sound stimuli and are protective against cisplatin ototoxicity in mouse models of cisplatin-induced hearing loss.…”
Section: Risk Factors That Enhance Cisplatin Toxicitymentioning
confidence: 99%
“…Previously, we showed that heat shock inhibits both cisplatin-and aminoglycoside-induced hair cell death (Cunningham and Brandon 2006). In addition to heat shock, noise exposure has also been shown to induce HSPs in the inner ear (Matsunobu et al 2009;Roy et al 2013).…”
Section: Introductionmentioning
confidence: 99%